NOISE PREDICTION, CALCULATION AND MAPPING USING SPECIALIZED SOFTWARE (Journal of Engineering Studies and Research, 2015)
This paper presents a set of software for prediction, calculation and noise mapping. These are useful both in assessing noise and adopting practical measures in order to reduce noise in areas with intense traffic. The software, through their working tools, allows making comparisons concerning noise before and after implementing noise reduction measures. The analyzed software's of noise prediction, calculation and mapping are specialized for noise generated by traffic.
Keywords: traffic noise; noise map; software; prediction